Exploration of Hospital Inpatients' Use of the Verbal Rating Scale of Pain - Bosdet, Luke; Herron, Katie; Williams, Amanda C. de C. (Frontiers in Pain Research, 2021)
Background: Assessment of pain largely relies on self-report. Hospitals routinely use pain scales, such as the Verbal Rating Scale (VRS), to record patients' pain, but such scales are unidimensional, concatenating pain intensity and other dimensions of pain with significant loss of clinical information. This study explored how inpatients understand and use the VRS in a hospital setting. Methods: Forty five participants were interviewed, with data analysed by thematic analysis, and completed a task concerned with the VRS and communication of other dimensions of pain. Results: Participants anchored their pain experience in the physical properties of pain, its tolerability, and its impact on functioning. Their relationship to analgesic medication, personal coping styles, and experiences of staff all influenced how they used the VRS to communicate their pain. Conclusion: Participants grounded and explained their pain in semantically similar but idiosyncratic ways. The VRS was used to combine pain intensity with multiple other elements of pain and often as a way to request analgesic medication. Pain scores need to be explored and elaborated by patient and staff, content of which will imply access to non-pharmacological resources to manage pain.